Plant oil bioconversion into increase biological activity through lipases derived from wastes - Francisco, Valesca Cristiane Benelli [UNESP]; Okino-Delgado, Clarissa Hamaio [UNESP]; Zanutto Elgui, Mirella R. [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; Facanali, Roselaine; da Silva, Rodrigo Augusto [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Marques, Márcia Ortiz Mayo; Fleuri, Luciana Francisco [UNESP] (Oxford University Press (OUP), 2019)
The aim of this study was to show that abundant and inexpensive plant oils can be biotransformed to increase biological activity (antioxidant, antimicrobial and cytotoxicity) through hydrolysis reaction catalysed by lipases. We tested homemade and commercial lipases through the biotransformation of nine different plant oils in forty different combinations. First, the chemical composition of the samples was investigated. Thereafter, biological tests were conducted to assess the antioxidant and antimicrobial activity of the sampled biotransformation products, as well as analyzed their influence on the viability of healthy and cancer cells. Summarising, sunflower, corn and olive oils modified by orange waste-obtained lipases presented the most promising results, reaching up to 90% of antioxidant activity increase and significant growth inhibition of bacteria colonies belonging to genera Escherichia, Listeria, Staphylococcus, Pseudomonas and Salmonella. In addition, those compounds affected human oral squamous carcinoma cells. The bioconversion of plant oils through lipases improves their biological properties and might be an option for biotechnological application.
Keywords: Antimicrobial; antioxidant; cytotoxicity; oils; orange enzymes